Mexico Financial Sector Assessment Program : Infrastructure Finance and Capital Markets -- Achievements and Challenges - World Bank Group; International Monetary Fund (World Bank, Washington, DC, 2017)
Mexico’s challenges in infrastructure finance can be framed along similar lines as other Advanced Economies (AEs) and large Emerging Market Economies (EMEs). Mexico is particularly well placed to make capital markets a reliable financing source complementing bank financing. Its capital markets are relatively mature, there is sufficient critical mass of long-term domestic institutional investors, and there is a relevant track record of innovative solutions for infrastructure financing from which to build. Section B of this Technical Note assesses the degree of maturity of the Mexican capital markets in those aspects that are most relevant for infrastructure financing. Section C discusses the different elements of the infrastructure financing ecosystem taking stock of the PPP framework and financial innovations that have been developed, with emphasis on impact, expected developments and potential improvements. Section D, discusses the role of development financial institutions in mobilizing private sector financing with emphasis on Banobras and Fonadin. Finally, section E concludes and provides a set of recommendations